Creating European citizens through citizenship, geography, and history education: A temporal and regional analysis of the Spanish curriculum - David García-Alvarez; Jonatan Arias-García (European Journal of Geography)
The European Dimension in Education (EDE) is a policy promoted by the Council of Europe and the European Union that aims to foster active, critical citizenship based on common democratic values. It is also associated with the idea of promoting better knowledge of the European Union and of the concept of European citizenship. Ever since the policy was initially launched, EU Member States have been trying to add a European dimension to their education systems, although little progress has been made. In this paper, we study the way EDE has been integrated into the Spanish education system. Our research is based on an analysis of the national and regional curricula for Social Sciences (Geography, History) and Citizenship Education in compulsory secondary education, as these are the main subjects within which Spanish students are taught civic education. Results showed few signs of progress in the integration of EDE into the Spanish curriculum. In fact, a regressive trend was observed in some cases. The curriculum has varied a lot over the years in line above all with the ideology of the national government. It has also varied considerably across Spain’s different regions, which play an important role in the inclusion of EDE contents in the curriculum. The inclusion of specific subjects on Citizenship Education has provided a considerable boost to the integration of EDE into the Spanish curriculum. However, EU-related content is usually scarce and is never considered as important as content explaining the Spanish political system, citizenship, geography and history.